Effects of pancrelipase on nonalcoholic fatty liver disease after pancreaticoduodenectomy. (20th June 2013) - Nagai, Minako; Sho, Masayuki; Satoi, Sohei; Toyokawa, Hideyoshi; Akahori, Takahiro; Yanagimoto, Hiroaki; Yamamoto, Tomohisa; Hirooka, Satoshi; Yamaki, So; Kinoshita, Shoichi; Nishiwada, Satoshi; Ikeda, Naoya; et al.
Abstract Background Postoperative nonalcoholic fatty liver disease (NAFLD) after pancreaticoduodenectomy (PD) has recently become recognized. However, the pathoetiology of postoperative NAFLD is largely unknown. Furthermore, the optimal treatment has not been established. The aim of this prospective study was to clarify whether pancrelipase, which contains digestive pancreatic enzymes, could reverse NAFLD. Methods A collaborative clinical trial has been conducted (UMIN000006841). A total of 30 patients who developed NAFLD after PD were prospectively treated with pancrelipase. NAFLD was defined and evaluated by the liver‐to‐spleen attenuation ratio on computed tomography (CT). Clinical symptoms and laboratory findings were also assessed. Results The mean liver‐to‐spleen CT ratio before surgery in 30 patients was 1.233. It declined to 0.453 at diagnosis of NAFLD. It was significantly improved by the treatment and the CT ratios at 1, 3 and 6 months after treatment were 0.762, 0.958 and 0.904, respectively (vs. pretreatment, P < 0.001). The mild liver dysfunction was also improved. Total protein, albumin and total cholesterol levels were significantly improved by the treatment. Importantly, relatively severe diarrhea seen in 11 patients was also ameliorated. Conclusions Pancrelipase has a significant beneficial impact on NAFLD after PD. Maldigestion after pancreatic surgery may be a main cause for the development of postoperative NAFLD.